2017
DOI: 10.1161/hypertensionaha.116.08526
|View full text |Cite
|
Sign up to set email alerts
|

Nonsteroidal Mineralocorticoid Receptor Antagonist Finerenone Protects Against Acute Kidney Injury–Mediated Chronic Kidney Disease

Abstract: Acute kidney injury induced by ischemia/reperfusion (IR) is a frequent complication in hospitalized patients. Mineralocorticoid receptor antagonism has shown to be helpful against renal IR consequences; however, the potential benefit of novel nonsteroidal mineralocorticoid receptor antagonists such as finerenone has to be further explored. In this study, we evaluated the efficacy of finerenone to prevent the acute and chronic consequences of ischemic acute kidney injury. For the acute study (24 hours), 18 rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
114
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(119 citation statements)
references
References 41 publications
3
114
0
2
Order By: Relevance
“…45 The protective effect of MR inhibition against the reduction in renal blood flow was mediated by increased NO production by endothelial NO synthase and the reduction of oxidative injury. [48][49][50] Moreover, it was determined that one of the mechanisms by which MR inhibition promotes adequate eNOS activation in ischaemic AKI is through a decrease in Rac 1-induced ROS generation in VSMCs, thus preventing sulfenic acid modification of the endothelin-B receptor and allowing proper signalling for eNOS activation, NO generation and thus adequate kidney perfusion. [48][49][50] Moreover, it was determined that one of the mechanisms by which MR inhibition promotes adequate eNOS activation in ischaemic AKI is through a decrease in Rac 1-induced ROS generation in VSMCs, thus preventing sulfenic acid modification of the endothelin-B receptor and allowing proper signalling for eNOS activation, NO generation and thus adequate kidney perfusion.…”
Section: Mrs In Kidney Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…45 The protective effect of MR inhibition against the reduction in renal blood flow was mediated by increased NO production by endothelial NO synthase and the reduction of oxidative injury. [48][49][50] Moreover, it was determined that one of the mechanisms by which MR inhibition promotes adequate eNOS activation in ischaemic AKI is through a decrease in Rac 1-induced ROS generation in VSMCs, thus preventing sulfenic acid modification of the endothelin-B receptor and allowing proper signalling for eNOS activation, NO generation and thus adequate kidney perfusion. [48][49][50] Moreover, it was determined that one of the mechanisms by which MR inhibition promotes adequate eNOS activation in ischaemic AKI is through a decrease in Rac 1-induced ROS generation in VSMCs, thus preventing sulfenic acid modification of the endothelin-B receptor and allowing proper signalling for eNOS activation, NO generation and thus adequate kidney perfusion.…”
Section: Mrs In Kidney Injurymentioning
confidence: 99%
“…45 More recently, it was reported that the non-steroidal MR antagonists BR-4628 and finerenone provide similar protection against ischaemic acute kidney injury (AKI). [48][49][50] Moreover, it was determined that one of the mechanisms by which MR inhibition promotes adequate eNOS activation in ischaemic AKI is through a decrease in Rac 1-induced ROS generation in VSMCs, thus preventing sulfenic acid modification of the endothelin-B receptor and allowing proper signalling for eNOS activation, NO generation and thus adequate kidney perfusion. 48,49 Indeed, cell-specific MR KO mice revealed that MR deficiency in VSMCs confers kidney protection in models of ischaemic and nephrotoxic injury to a level similar to that observed with MR antagonists.…”
Section: Mrs In Kidney Injurymentioning
confidence: 99%
“…Several recent studies have indicated a role for MR in AKI by demonstrating that MR antagonism reduces ischemia reperfusion injury in a rat model of AKI (Barrera-Chimal et al . 2016, Lattenist et al . 2017).…”
Section: Vascular Mr In Cardiovascular Pathologiesmentioning
confidence: 99%
“…Experimental evidence in rodent models of acute kidney injury (AKI) supports the concept that MR contributes to vascular tone regulation [1]. The benefit of MRA in renal ischemia-reperfusion injury is associated with improved renal hemodynamics and decreased renal vascular resistance [21,22]. We recently showed that MR expressed in mouse smooth muscle cells contributes to renal injury induced by ischemia (through a mechanism involving oxidative stress and Rac1 activation) [23], as well as in acute CsA nephrotoxicity (due to increased vascular L-type calcium channel activity thereby resulting in decreased renal artery vasoconstriction and overall improvement in renal hemodynamics) [24].…”
Section: Mr and Renal Hemodynamic Alterationsmentioning
confidence: 99%
“…In vascular cells, aldosterone increased ROS which in turn modifies the cysteinyl thiols in the eNOS-activating region of endothelin-1 B receptor to decrease endothelin-1-stimulated eNOS activity, impairing the vasodilatory pathway. These effects have repercussions on renal hemodynamics and function in kidney ischemia/reperfusion injury in both rat and mouse [21][22][23]. In rat mesangial cells, aldosterone directly stimulates superoxide anion generation, which is accompanied by an increase in NADPH oxidase activity and translocation of p47phox and p67phox to the cell membrane [28].…”
Section: Mr and Oxidative Stressmentioning
confidence: 99%